Doctoral Programs in Mathematics Education: Should Programs be Accredited? - Robert Reys (Journal of Mathematics Education at Teachers College, 2018)
Over several hundred different institutions in the USA have graduated people identifying a doctorate in mathematics education. Some institutions graduate people every year, other institutions graduate one person every 3-5 years. Some institutions have one faculty member, others have more than ten. There is no agreed upon common core of knowledge or requirements for a doctorate in mathematics education. This article discusses some pros and cons of accreditation, offers some direction, and hopefully will stimulate thinking about accreditation for doctoral programs in mathematics education.